IDENTIFIKASI POTENSI FISIK PESISIR PANTAI WISATA BAHARI KELURAHAN TELUK KABUNG SELATAN KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Ilhamdi Bagus Perdana; yurni suasti; ahyuni aziz (JURNAL GEOGRAFI, 2016)
This study aims to (1) Knowing the physical potential supporters South Teluk Kabung Village nautical tourism attractions. (2) Identify the availability of accessibility South Teluk Kabung Village. (3) Identify the availability of means of support South Teluk Kabung Village nautical tourism. (4) Identify the development of marine tourism attraction in South Teluk Kabung Village. This research is quantitative descriptive, using the techniques of data collection by observation and documentation, as well as using data from institutions Loka Resources Research and Coastal Vulnerability "LPSDKP". The population in this study is the coastal area South Teluk Kabung Village, sampling technique in this research is purposive sampling by taking nine locations scattered South Teluk Kabung Village sample, the sample in this study is a landform marine and alluvial landform. This study found that: (1) Physical potential South Teluk Kabung Village coast consists of wide beach is 9-18 meters measured from the low water mark to the high water mark, the shape of the beach is a sandy beach, reef conditions found in living keadan, dominant land cover is a shrub and palm trees, beach slope of 0.8% -1.45% by criteria flat beach, ocean depths of 5-40 meters, flow velocity 8:12 to 9:33 m / sec, (2) accessibility lower classification with a score of 16, (3) a means moderate classification travel with a score of 5, (4) Things to suite developed marine tourism in coastal areas South Teluk Kabung Village is camping, recreation, snorkeling and diving.